UNDERSTANDING SMK TEACHER IN CURRICULUM IMPLEMENTATION 2013 REVISION 2017 IN BANTEN PROVINCE - Sulaeman Deni Ramdani; Angga Pangestu (VANOS Journal of Mechanical Engineering Education, 2018)
This study aims to find out how much understanding of SMK teachers in the implementation of the 2013 revision curriculum 2017. Curriculum issues 2013 revision 2017 is the preparation of Learning Implementation Plan (RPP), learning activities and implementation of assessment. Understanding teachers less will have an impact in the learning process because the learning itself is a reference curriculum in the delivery of material, so that the learning process does not work properly. The government's strategy to prepare teachers in the implementation of the 2013 curriculum of 2017 revision from socialization, training, mentoring and evaluation has been implemented, so that the new curriculum is going well. This research is descriptive qualitative research. The method used is descriptive. The subjects of this study were teachers of SMKN 1 Cikande, SMKN 2 Serang City, SMKN 1 Cilegon City and SMKN 2 Pandeglang City. Data collection techniques used were questionnaires and interviews. Based on the results of the researchers do with data collection techniques and interviews using eight indicators 1) syllabus, 2) details of the effective week, 3) annual programming, 4) semester program, 5) core competence / basic competency 6) learning implementation plan, 7) academic calendar and 8) evaluation tools conclude that SMK teachers in Banten have an understanding of the 2017 revision curriculum in 2017 including the good category with the percentage of 80%. The results of the understanding of the 2013 revised curriculum 2017 in Banten Province is the lack of monitoring and training conducted by the government and the school, so that teachers do not all understand and implement the curriculum.